Direct Learning And ARCS (Attention, Relevance, Confidence, Satisfaction) : Which Learning Model Influences Statistical Reasoning? - Zalma Amandah Zaliki; Suhar; Moh. Salam (Jurnal Amal Pendidikan, 2024)
Reasoning ability refers to what students can do with statistical material and how they can use statistical concepts to solve statistical problems. One way to measure students' statistical reasoning is to use a learning model that emphasizes statistical reasoning abilities . Study This use method experiment pseudo with take sample 1 class experiment and 1 class control . Study This aim For know description of the ARCS learning model in the material statistics to ability reasoning statistics student class VIII MTs Negeri 02 Bombana , Para know there is influence of the ARCS learning model on the material statistics to reasoning statistics student class VIII MTs Negeri 02 Bombana . Based on results study obtained ability reasoning statistics student MTsN 02 Bombana taught with the ARCS ( Attention, Relevance, Confidence, Satisfaction ) learning model average score 69.11 from 30 students as well as liveliness student during four meetings consecutive are 76.63%, 82.89%, 86.84%, 90.78%. Based on hypothesis testing of average ability reasoning statistics taught students with the ARCS model ( Attention, Relevance, Confidence, Satisfaction ) more tall than the students being taught with a learning model direct . So you can withdrawn conclusion that exists criteria significant influence towards the ARCS learning model.